Health Implications of Anabolic-Androgenic Steroids: Usage, Risks, and Treatment Approaches - The Literature Review - Jodłowski, Krzysztof; Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria; Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Broda, Aleksandra; Hoksa, Kacper (Quality in Sport, 2025)
Anabolic-androgenic steroids (AAS) are commonly used to enhance athletic performance and physical appearance, but their abuse is linked to a range of serious health consequences, including cardiovascular, liver, and psychological disorders, as well as infertility. Despite the growing concern over AAS misuse, current research is limited by methodological constraints, including a lack of randomized controlled trials and long-term studies. The review explores the health implications of AAS use, highlighting the importance of an interdisciplinary approach to managing AAS-related health issues, emphasizing harm reduction, pharmacological interventions, and fertility preservation techniques. It also underscores the need for improved healthcare support, education, and trust-building to address the challenges associated with AAS abuse effectively. Furthermore, the review highlights significant gaps in the literature, such as the absence of comprehensive guidelines for harm reduction and the scarcity of longitudinal data on the long-term effects of AAS. The findings suggest a critical need for continued research, better medical management, and societal interventions to mitigate the risks associated with AAS use and provide effective care for affected individuals.